Indian Banks and Basel-II: An Econometric Analysis - Gupta, N. L.; Mehta, Meera (Indian Journal of Finance, 2011)
The New Basel Capital Accord, often referred to as the Basel II Accord or simply Basel II, intends to strengthen the soundness and stability of the international banking system and reduce competitive inequalities between banks. Although the Basel Capital Accord of 1988 (or Basel I) was a milestone in ensuring effective banking supervision, subsequent changes in the banking industry, financial markets, risk management and bank supervision, as well as financial crises such as that in South- East Asia and East Asia in 1997-1998, led the Basel Committee on Banking Supervision to issue a revised Basel II guidelines in June 2004. The new accord aims to overcome the anomalies of the present system. It emphasizes on bank's own internal methodologies, supervisory review and market discipline. The primary objective of the new Accord is to make it more risk sensitive and thus strengthen banking systems even in periods of financial crisis. Consequently, the new proposal moves ahead of the "one-size-fits-all" approach and adopts a methodology for gauging capital adequacy ratios based on credit risk, while also incorporating charges for operational risk. This paper attempts to examine the various aspects of Basel II guidelines and impact of Basel II on Capital to Risk Asset ratio (CRAR), which is expected to capture the regulatory pressure on banks' lending and ratio of Non-performing assets (NPAs) to total advances as measure of banks' financial health. The study concludes that Basel II regulations have led to significant improvement in the risk structure of banks as their capital adequacy has improved. The NPAs for both Public sector as well as private sector banks have declined. Also there exists a negative relationship between CAR and NPAs, which clearly indicates that due to capital regulation, banks have to increase their CAR which led to the decrease in NPAs.